THU0093 EARLY REMISSION IS ASSOCIATED WITH LOWER FATIGUE LEVELS ON THE LONG TERM IN PATIENTS WITH RECENT ONSET RHEUMATOID ARTHRITIS. (2nd June 2020) - De Cock, D.; Nooyens, A.; Bertrand, D.; Stouten, V.; Pazmino, S.; Joly, J.; Westhovens, R.; Verschueren, P.
Abstract : Background: Fatigue is mentioned as a symptom with high impact in many patients with Rheumatoid Arthritis (RA) and this symptom remains difficult to be managed by both the patient and the physician. Objectives: To investigate if rapid suppression of disease activity in early RA could impact fatigue complaints in the long run. Methods: For this study, we included patients from the 2-year pragmatic investigator-initiated Care in Early Rheumatoid Arthritis (CareRA) trial. Most patients were treated intensively, with different combinations of csDMARDs and glucocorticoid remission induction schemes, except one group without classic markers of poor prognosis that was treated with MTX weekly in monotherapy. Patients were followed up at least every 3 months, with more mandatory visits in the first 6 months of treatment. Clinical parameters including DAS28 components were registered at every visit. Fatigue was measured by the multi-dimensional fatigue inventory (MFI), a self-reported instrument consisting of 20 questions with a Likert scale from 1-5 as answer. These 20 questions can be subdivided in five subscales (0-20) of four questions (higher scores indicating higher fatigue levels): general fatigue, mental fatigue, physical fatigue, reduced activity and reduced motivation. General fatigue means the general feeling of being tired. Mental fatigue implicates concentration and memory problems. Physical fatigue implicates a lack of energy and strength. Reduced activity means that patients can do less activities for example on one day. Reduced motivation means that patients don't want to plan or do things due to no motivation. MFI was obtained at baseline, at week 16, week 52 and week 104. Only patients with a filled-out MFI at baseline and available DAS28CRP at week 16 were included in this study. Patients were divided in 2 groups based on their response, defined as achieving or not achieving DAS28CRP remission (<2.6) at week 16. These patients were classified as early responders and controls respectively. The 2 groups were compared by Mann-Whitney-U test. A generalized estimating equation (GEE) compared the 2 groups over the course of the 2-year trial per each of the 5 domains of the MFI, adjusting for baseline DAS28CRP and baseline MFI domain score. Results: Of the 379 patients recruited in the CareRA trial, 343 (90.5%) had a MFI score available at baseline and a DAS28CRP available at week 16 with 236 (68.8%) patients achieving remission, and 107 (31.2%) patients not achieving remission at week 16. After 2 years of treatment, the proportion of patients in DAS28CRP remission was still higher in the early responders versus controls (82.3% versus 63.5%, p=0.001). Every MFI domain after 2 years of treatment showed lower scores for early responders including general fatigue (p=0.017), physical fatigue (p=0.011), reduced activity (p=0.040) and mental fatigue (p=0.042) except reduced motivation (p=0.062) (see figure 1 ). GEE analysis demonstrated that all MFI domains differed over 2 years between patients in remission or not at week 16, including general fatigue (p<0.001), physical fatigue (p<0.001), reduced activity (p<0.001), mental fatigue (p=0.037) and also reduced motivation (p=0.005). Conclusion: Patients reaching remission after 16 weeks of treatment achieve lower fatigue levels over 2 years compared to patients not reaching this early remission. This study underlines the importance of early disease control. Successful early intensive treatment improves in the long run not only clinical outcomes but also an important patient preferred outcome such as fatigue. Disclosure of Interests: Diederik De Cock: None declared, Amber Nooyens: None declared, Delphine Bertrand: None declared, Veerle Stouten: None declared, Sofia Pazmino: None declared, Johan Joly: None declared, Rene Westhovens Grant/research support from: Celltrion Inc, Galapagos, Gilead, Consultant of: Celltrion Inc, Galapagos, Gilead, Speakers bureau: Celltrion Inc, Galapagos, Gilead, Patrick Verschueren Grant/research support from: Pfizer unrestricted chair of early RA research, Speakers bureau: various companies